Performance and metabolism of ruminants fed with Bacillus licheniformis and Bacillus subtilis - Arthur, Bruno Augusto Valverde (2023)
The use of antibiotics as a feed additive for animals is gradually banned due to the risk of residue accumulation in animal products and the emergence of antibiotic-resistant bacterial strains. As an alternative to meeting the desire for greater sustainability in food production, probiotics emerge. This product\'s action is to modify the rumen environment by stimulating the growth of microorganisms, stabilizing pH, changes in the microbiota fermentation pattern and increasing digestibility and use of nutrients, especially the microorganisms evaluated in the current work that have the characteristic of greater use of nutrients, altering rumen fermentation towards greater propionate synthesis. The objective of this work was to evaluate the effect of probiotics based on Bacillus licheniformis (1.6x109 CFU/g) and Bacillus subitilis (1.6x109 CFU/g) on animal performance, ingestive behavior and apparent digestibility in the total tract in large ruminants. For the animal performance study, sixty Holstein cows were used; these animals were blocked by milk production (21.1 ± 4.5 kg/d), days in lactation (139.93 ± 72.5 days) and live weight (536.2 ± 58.6 kg) and whether they were primiparous or multiparous. The cows received the same silage-based diet, varying only the treatment (CON calcium carbonate or PROB probiotic) that was added to each cow\'s diet once a day in the morning (3 g/d), together with a solution of sugar to adhere the product and increase palatability for immediate consumption of the probiotic. Eighteen male Nelore animals were used to study nutrient digestibility, fistulated in the rumen, 16 of them in frame blocks and randomized in stalls for diet consumption. Thus, 8 animals were allocated per treatment (with or without probiotic). The other two animals were used to determine the iNDF of samples from the animal performance experiment. The bulls received the same diet and were fed in the same way as the animals in the previous experiment. Data were analyzed using the PROC MIXED procedure from SAS (SAS Inst., Inc., Cary, NC) for a randomized complete block design. The statistical model included the fixed effect of treatment and the random effect of blocking. The differences occurred in the reduction in dry matter consumption of PROB animals, without changing milk production, thus increasing feed efficiency. The composition of the milk was also modified, with an increase in fat (%) for PROB animals and a tendency towards a reduction in protein (%) for them, resulting in greater protein production (kg/d), still in terms of milk characteristics, PROB animals had lower MUN (mg/dL) compared to CON. Total dry matter digestibility was higher for PROB, as well as NDF and starch digestibility, with only crude protein digestibility being lower for PROB compared to CON. Plasma glucose was higher for PROB at all times collected after the first meal (0, 1, 2, 3, 6h) with the exception of 12h where the CON treatment showed higher plasma glucose. BUN was lower at all times collected after the first meal for PROB treatment (0, 1, 2, 3, 6 and 12h). In the data collected in the nutrient digestibility work with Nelore cattle, rumen ammonia values (mg/dL) were lower for PROB at 0h after the first meal and higher for PROB at 24h after the first meal and showed a tendency to be lower at other times for PROB after the first meal (12, 48 and 72h). Rumen pH was higher for PROB at all collection times after the first meal. In conclusion, the probiotic was effective in increasing the feed efficiency of lactating animals.